Acute Telogen Effluvium in Patients Recently Infected with SARS-CoV-2 - Ângela Roda; Rui Oliveira-Soares (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Introduction: The hair cycle is especially susceptible to endogenous and exogenous stimuli, including febrile states and emotional stress, which are a constant in this pandemic era. In this case series, we describe the clinical characteristics of patients recently diagnosed with SARS-CoV-2 infection who developed acute telogen effluvium. Material and Methods: We performed a registry of patients with laboratory-confirmed SARS-CoV-2 infection who developed acute telogen effluvium and actively sought medical care at the Hair Unit of Dermatology Center of CUF Descobertas Hospital, from March 2020 to October 2020. Patient demographics, the month of SARS-CoV-2 infection diagnosis, COVID-19 associated symptoms, latency of telogen effluvium, duration of hair loss, and associated scalp symptoms were recorded. Results: Twenty-seven patients recently diagnosed with SARS-CoV-2 infection presented with acute telogen effluvium. Of them, 5 (18.5%) patients mentioned trichodynia. The median time of latency of increased hair loss since SARS-CoV-2 infection diagnosis was 10 weeks. In a third of cases (n=9, 33.3%), hair loss occurred early (with a latency period of 3 weeks or less). The resolution of telogen effluvium was documented in 16 (59%) cases with a median duration of hair loss of 24.5 days. The most common symptoms of COVID-19 were fever (n=17, 63%), ageusia (n=8, 30%), cough (n=6, 22%), myalgia (n=5, 18.5%), anosmia (n=4, 15%), and thoracalgia (n=3, 11%). Four patients (15%) with SARS- -CoV-2 infection were asymptomatic for COVID-19. Discussion: Acute telogen effluvium corresponds to a delayed consequence of an abnormal shift in the hair cycle from anagen to telogen, which is responsible for premature hair shedding, occurring approximately two to three months after a triggering event. Viral illnesses and febrile states are known causes. Regarding SARS-CoV-2 infection, we hypothesize that viral cytopathic effects and inflammatory or immune responses may affect hair follicles and explain hair loss and trichodynia. Conclusion: Our case series presents the first comprehensive collection of patients with acute telogen effluvium following SARS-CoV-2 infection. Interestingly, in a third of our cases, telogen effluvium developed within the first 3 weeks of SARS-CoV-2 infection. Based on these data, we propose that this finding should be considered in COVID-19, especially at the convalescent phase.